Current Control System for Coupled Coil Arrays in MPI - Scheel, Jan-Philipp; Foerger, Fynn; Sevecke, Florian; Knopp, Tobias (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Magnetic Particle Imaging (MPI), a novel biomedical imaging technique, maps the spatial distribution of superparamagnetic tracers. One challenge in upsizing the imaging systems from small animal to human-size is the power consumption. An energy-efficient topology for selection and focus field generators was presented using coupled multi-coil arrays. A trivial, cost-intensive solution to drive these arrays is the usage of separate 4-quadrant amplifiers for each coil. In this paper a cost-efficient and scalable alternative is presented. A current controlled design achieves currents of up to 30 A with frequencies up to 10 Hz and suppresses the inductive coupling within the arrays.